Core Procedural Skills to be Taught for III-Year Undergraduate Medical Students: A Modified Delphi Study - MASANAM KASI SUMATHY; ZAYABALARADJANE ZAYAPRAGASSARAZAN; DINKER RAMANANDA PAI; MUKTA WYAWAHARE (Journal of Advances in Medical Education and Professionalism, 2024)
Introduction: While medical students are expected to learn procedural skills during their training, there is no consensus on their level of learning. Further, the most essential procedural skillsacross medical curricula which need to be taught during their III-year clinical posting are often not considered. The purpose of this study was to identify the core procedural skills needed to be taught during the III-year undergraduate medical students clinical posting.Methods: A three-round, online Modified Delphi method was used to identify consensus on selecting the most essential procedural skills prescribed in National Medical Commission(NMC) curriculum 2019. In Round 1, a list of 54 procedural skills from the National Medical Commission's (NMC) Graduate Medical Education Regulations (GMER) 2019 curriculum wasdistributed to 22 experts in pre-clinical medical education and multidisciplinary clinicians. They rated the skills in terms of importance. In Round 2, the skills that received consensus in Round 1 were presented, resulting in 13 skills for evaluation. Round 3 further narrowed down the skills to a final consensus of 6. An interclass correlation coefficient of 0.767 among experts indicates a substantial level of reliability.Results: Consensus was achieved for six procedural skills, each demonstrating over 80% agreement among the experts. These skills include basic life support, intravenous cannulation, urinary catheterization for both male and female patients, nasogastric tube insertion, oxygen administration, and basic suturing. Notably, all these skills received the highest level of agreement, surpassing 90% consensus.Conclusions: The results of the modified Delphi study offer crucial insights into the procedural skills that should be included in the curriculum for third-year undergraduate medical students during their clinical rotations in a tertiary care teaching hospital. Faculty members at these institutions differ in their opinions regarding the importance of teaching specific procedural skills, influenced by their teaching background and the student cohorts they instruct. From a comprehensive list, six skills have been pinpointed as the most vital through the modified Delphi technique. Moreover, the Delphi technique is acknowledged as a valuable method for achieving aconsensus on prioritizing the training of certifiable skills.